2022
DOI: 10.1007/s10517-022-05561-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MARK ERK1/2 and p38 in Regulation of Functions of Neural Stem Cells and Neuroglia under Conditions of β-Amyloid-Induced Neurodegeneration

Abstract: The role of ERK1/2 and p38 in the realization of the growth potential of neural stem cells and secretion of neurotrophic growth factors by glial cells was studied using in vitro model of β-amyloid-induced neurodegeneration. It was shown that amyloid-β fragment 25-35 significantly inhibits the cell cycle progression of neural stem cells against the background of stimulation of their differentiation and reduced production of growth factors by neuroglia. The inhibitory role of ERK1/2 and p3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…In the aging process, NGF deprivation or NGFR loss also leads to cell cycle deficit . A study indicated that β-amyloid inhibits the cell cycle progression of NSC and reduces the production of growth factor . Therefore, in addition to reducing neuronal cell death, increasing cell viability is an alternative treatment option for neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the aging process, NGF deprivation or NGFR loss also leads to cell cycle deficit . A study indicated that β-amyloid inhibits the cell cycle progression of NSC and reduces the production of growth factor . Therefore, in addition to reducing neuronal cell death, increasing cell viability is an alternative treatment option for neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…34 A study indicated that β-amyloid inhibits the cell cycle progression of NSC and reduces the production of growth factor. 35 Therefore, in addition to reducing neuronal cell death, increasing cell viability is an alternative treatment option for neurodegeneration. Sang proposed that the NGF and the PI3K/Akt signaling pathway participate in neuroprotection and curcumin upregulates this pathway.…”
Section: Discussionmentioning
confidence: 99%